Evaluation of Student Preference for Printed Books and E-books: A Quantitative Study - Bojiah, Janaki; Praveena, V. (Journal of Engineering Education Transformations, 2025)
People tend to embrace emerging technologies to make their lives easier in every possible aspect. This has its impact in the field of education as well in terms of pedagogies, interactive tools, learning management systems, and more specifically instructional materials. Amongst the instructional materials, e-books have recently become popular in the sphere of education. It gained popularity during the pandemic situation when the shops were shut to get printed books which reinforced students to adopt e-books. This study intends to find the preference of the students of Velammal College of Engineering & Technology in Madurai with respect to e-books (not the interactive ones) and printed books so that the results can facilitate in decision making as to what kind of sources the educationists should invest on. A survey was conducted using a structured five-point Likert scale questionnaire. It was shared with the students and their responses were recorded. Random sampling method was used for the choice of the participants. Cronbach alpha test was carried out to verify the reliability of the questionnaire. Having carried out the t-test to check whether the two groups vary from each other, the comparative analysis research methodology was used for data analysis. This study also deals with the pros and cons of both e-books and printed books based on the survey. The results of the study confirms that the students still seem to prefer printed books over e-books. The findings suggest that the educationists should prioritize student preferences and ensure the availability of light weight printed books everywhere.